1998
DOI: 10.1016/s0960-9822(98)70298-2
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of Cdc20 proteolysis reveals a role for the APC components Cdc23 and Cdc27 during S phase and early mitosis

Abstract: There are remarkable differences in the regulation of Cdc20 and Cdh1/Hct1. Furthermore, the APC activator Cdc20 is itself a substrate of the Cdc27 have a role in the degradation of Cdc20 during S Phase and early mitosis that is not mediated by its destruction box.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
220
2
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(233 citation statements)
references
References 47 publications
10
220
2
1
Order By: Relevance
“…Full activation of APC Cdh1 arises by a lowering of overall Cdk activity through APC Cdc20 activity and release of Cdc14 phosphatase through the mitotic exit network and associated pathways (Visintin et al, 1999;Stegmeier et al, 2002). Furthermore, to smooth the transition from APC Cdc20 to APC Cdh1 , APC Cdh1 is able to mediate the destruction of APC Cdc20 in late mitosis (Prinz et al, 1998;Shirayama et al, 1998). Targeted proteolysis thus reinforces the feedback loop that ultimately raises APC Cdh1 levels over that of APC Cdc20 Peters, 2002).…”
Section: Iκkα and Iκkβmentioning
confidence: 98%
“…Full activation of APC Cdh1 arises by a lowering of overall Cdk activity through APC Cdc20 activity and release of Cdc14 phosphatase through the mitotic exit network and associated pathways (Visintin et al, 1999;Stegmeier et al, 2002). Furthermore, to smooth the transition from APC Cdc20 to APC Cdh1 , APC Cdh1 is able to mediate the destruction of APC Cdc20 in late mitosis (Prinz et al, 1998;Shirayama et al, 1998). Targeted proteolysis thus reinforces the feedback loop that ultimately raises APC Cdh1 levels over that of APC Cdc20 Peters, 2002).…”
Section: Iκkα and Iκkβmentioning
confidence: 98%
“…The affinity of activators of the APC is regulated by phosphorylation of APC subunits (Kotani et al, 1999;Kramer et al, 2000;Kraft et al, 2003). Cdc20 activity is regulated by transcription and APC Cdh1 -dependent degradation leading to APC Cdc20 activity from early mitosis until the M to G1 transition (Fang et al, 1998b;Prinz et al, 1998;Shirayama et al, 1998;Pfleger and Kirschner, 2000;Huang et al, 2001). Cdk1 and MAPK can phosphorylate Cdc20; although it is controversial whether phosphorylation of Cdc20 is necessary for APC activation in human cells (Kotani et al, 1999;Kramer et al, 2000;Yudkovsky et al, 2000), it is required for its inhibition by the spindle checkpoint (Chung and Chen, 2003).…”
Section: Regulation Of Apc Activitymentioning
confidence: 99%
“…Initially it has been reported that the protein level of Cdh1 remains relatively constant throughout the cell cycle (Fang et al, 1998b;Prinz et al, 1998) and Cdh1 is activated by dephosphorylation from the M to G1 transition until the end of the G1 phase Jaspersen et al, 1999;Lukas et al, 1999;Kramer et al, 2000). However, there are also reports that Cdh1 levels oscillate during the cell cycle at least in human cells Hsu et al, 2002).…”
Section: Regulation Of Apc Activitymentioning
confidence: 99%
“…Under normal conditions, the anaphase-promoting complex/cyclosome (APC/C) 1 promotes the ubiquitination of Pds1, leading to its degradation, and consequently the activation of Esp1 (13,14). The ability of the APC/C to ubiquitinate Pds1 depends on the physical association between Pds1 and an APC/C-associated protein, Cdc20 (15)(16)(17)(18). Specifically, abolishing the binding of Pds1 to Cdc20 prevents Pds1 ubiquitination (17,18).…”
mentioning
confidence: 99%
“…Specifically, abolishing the binding of Pds1 to Cdc20 prevents Pds1 ubiquitination (17,18). Cdc20, and its homolog Cdh1, belong to a family of WD-repeat proteins that confer substrate specificity to the APC/C (15,16). Cdc20 is active early in mitosis and is involved in the ubiquitination of several cell cycle regulators, including Pds1 and the cyclins Clb5 and Clb2 (19 -21).…”
mentioning
confidence: 99%